Physical chemistry : A Molecular Approach - McQuarrie, Donald A. (New Delhi Viva Books, 2011)
As the first modern physical chemistry textbook to cover quantum mechanics before thermodynamics and kinetics, this book provides a contemporary approach to the study of physical chemistry. By beginning with quantum chemistry, students will learn the fundamental principles upon which all modern physical chemistry is built. The text includes a special set of "Math Chapters" to review and summarize the mathematical tools required to master the material. Thermodynamics is simultaneously taught from a bulk and microscopic viewpoint that enables the student to understand how bulk properties of materials are related to the properties of individual constituent molecules. This new text includes a variety of modern research topics in physical chemistry as well as hundreds of worked problems and examples.
Keywords: chemistry,physical chemistry